Molecular Characterization, Hematobiochemical Changes and Therapeutic Management of Tick Born Haemoparasites in Naturally Infected Cattle - Mohamed, Haidy E.; Ibrahim, Hala N.; Sallam, Nahla H. (Journal of Advanced Veterinary Research, 2023)
In this study, examination of infected cattle infested with tick, identification of collected tick samples were based on the12S rDNA PCR products as Rhipicephalus annulatus, the GenBank accession number is (OP650242). A total of 72 blood samples from crossbred cattle of both sexes were examined clinically and in the laboratory. Out of these, 43 cattle were healthy, while 19 (26.38%) had theileriosis and 10 (13.88%) had babesiosis. Hemogram analysis revealed distinct anemia patterns, with Babesia-infected cattle displaying macrocytic hypochromic anemia and theileria-infected ones showing normocytic normochromic anemia, both with reduced platelet counts. Babesia-infected cattle had elevated total leukocyte counts, neutrophilia, eosinophilia, and lymphopenia, while Theileria-infected cattle had decreased total leukocyte counts, neutropenia, lymphocytosis, and eosinophilia. In infected cattle, serum biochemistry showed increased ALT, AST, creatinine, and urea levels in both Babesia and Theileria infections. There was decreased serum protein, and albumin, in both cases. Oxidative stress revealed elevated serum malonaldehyde (MDA), reduced glutathione peroxidase (GPx) andÂ Â catalase (CAT) levels in infected animals compared to controls. After administering Imidocarb dipropionate (1mg/kg S/C) and Buparvaquone (1ml/20kg I/M) to animals with babesiosis and theileriosis, respectively, there was a positive change in the hematological and biochemical measures, bringing them closer to the normal values. There is a genuine danger to the cattle industry in Egypt due to the existence of babesiosis, theileriosis, and their vector. Modern techniques like PCR should be utilized for precise monitoring and to prevent spread of such diseases. Furthermore, adverse effect of babesia and theileria on hematological and biochemical parameters can be eliminated through the appropriate use of Imidocarb dipropionate and Buparvaquone for babesiosis and theileriosis respectively.